PENGARUH KOMBINASI EKSTRAK JERUK BRASTAGI DAN WORTEL PER ORAL SEBELUM AKTIVITAS FISIK TERHADAP PENURUNAN KADAR MDA PLASMA MENCIT SETELAH AKTIVITAS FISIK - Nurvidya Rachma Dewi; Ambrosius Purba; Beltasar Tarigan (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2018)
Aerobic metabolism at the cellular level generates free radicals. Under normal conditions, there’s a balance between free radicals and endogenous antioxidants. An excessive amount of free radicals impair DNA, protein, fat, etc. The level of free radicals can be known by measuring plasma malondialdehyde level. Combination of Brastagi’s oranges and carrots juice as exogenous antioxidants supplementation expected to decrease free radicals level. The aim of this study is to investigate the difference of plasma MDA level during several time intervals on mice which are given and not given a combination of Brastagi’s oranges and carrots juice before physical activity using mice’s treadmill for 20 minutes. The research method used in this study is an experimental laboratory study. The objects of this study are 40 mice (mus musculus), white-colored, male, weighting 25-30 grams, which is randomly chosen. The objects are divided into 2 groups, Group A: 20 mice (given a combination of Brastagi’s oranges and carrots juice before physical activity using mice’s treadmill) and group B: 20 mice (not given a combination of Brastagi’s oranges and carrots juice before physical activity using mice’s treadmill). Group A is divided into 5 subgroups: A1 (measurement of plasma MDA level at 0 minutes after treadmill), A2 (measurement of plasma MDA level at 15 minutes after treadmill), and A3 (measurement of plasma MDA level at 30 minutes after treadmill), A4 (measurement of plasma MDA level at 60 minutes after treadmill), and A5 (measurement of plasma MDA level at 240 minutes after treadmill). The same procedures are employed for group B. Plasma MDA level measured after doing a physical activity using mice treadmill. The homogeneity of the result then was tested using Levene’s test and the normality of the result was tested using the Kolmogorov-Smirnov test (p>0.05). Further, the data were analyzed using an independent t-test (p≤0.05), one-way ANOVA (p≤0.05) then Duncan’s test were used. The results reveal significant lowering plasma MDA concentration in mice receiving a combination of Brastagi’s oranges and carrots juice before physical activity, which is measured during several time intervals: 0,15,30,60, and 240 minutes after physical activity than in mice not receiving a combination of Brastagi’s oranges and carrots juice before physical activity. The MDA level differences between groups that are given and not given combination of Brastagi’s orange and carrots juice before physical activity measured during several intervals are 11,44% (0,8920 vs 1,0071) measured 0 minutes after physical activity, 15,47% (0,7902 vs 0,9348) measured 15 minutes after physical activity, 14,42% (0,7473 vs 0,8732) measured 30 minutes after physical activity, 11,35% (0,6696 vs 0,7554) measured 60 minutes after physical activity, and 13,60% (0,5786 vs 0,6696) measured 240 minutes after physical activity.The conclusion of the study suggested that a combination of Brastagi’s orange and carrots juice supplementation has a lowering effect toward plasma MDA level measured during several time intervals.